2012
DOI: 10.1161/circulationaha.111.071100
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Vaccination and Major Adverse Vascular Events in High-Risk Patients

Abstract: Background-We sought to determine the association between influenza vaccination and major adverse vascular events because the association remains uncertain. Methods and Results-A total of 31 546 participants were enrolled from 40 countries. Eligibility included age Ն55 years and known vascular disease. The primary outcome was a composite of death resulting from cardiovascular causes, myocardial infarction, or stroke during 4 influenza seasons (2003)(2004)(2005)(2006)(2007). Influenza vaccination was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
38
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 45 publications
(84 reference statements)
1
38
0
Order By: Relevance
“…28 For example, one recent study using a large clinical database from 2 randomized trials (the ONTARGET and TRANSCEND trials), which enrolled 31,546 patients with a history of vascular disease (approximately 20% had a previous stroke or TIA) or diabetes mellitus with end-organ damage, assessed the association between influenza vaccination and the risk of a major vascular event using a propensity score, but with different covariates, including markers of healthy living. 15 This study found that influenza was associated with a strong decrease in major vascular events (31%-48%). However, the authors concluded that despite all efforts to limit bias, undetected bias probably explained their results, because a similar benefit association was found outside the epidemic period and a greater effect was observed for noncardiovascular death (ranging from 73% to 79%), which is not supposed to be influenced by influenza vaccination.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…28 For example, one recent study using a large clinical database from 2 randomized trials (the ONTARGET and TRANSCEND trials), which enrolled 31,546 patients with a history of vascular disease (approximately 20% had a previous stroke or TIA) or diabetes mellitus with end-organ damage, assessed the association between influenza vaccination and the risk of a major vascular event using a propensity score, but with different covariates, including markers of healthy living. 15 This study found that influenza was associated with a strong decrease in major vascular events (31%-48%). However, the authors concluded that despite all efforts to limit bias, undetected bias probably explained their results, because a similar benefit association was found outside the epidemic period and a greater effect was observed for noncardiovascular death (ranging from 73% to 79%), which is not supposed to be influenced by influenza vaccination.…”
Section: Discussionmentioning
confidence: 79%
“…However, the authors concluded that despite all efforts to limit bias, undetected bias probably explained their results, because a similar benefit association was found outside the epidemic period and a greater effect was observed for noncardiovascular death (ranging from 73% to 79%), which is not supposed to be influenced by influenza vaccination. 15 We were unable to confirm vaccination history with medical records, and some patients may have been misclassified, although self-report of vaccination history has a high sensitivity and specificity. 31 More importantly, we cannot exclude an immortality time bias, despite propensity score-matched analysis.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The study designs to identify such ''agents'' require both frequent contact with participants and better methods of identification of possible ''agents,'' e.g. air pollution, psychosocial stressors, infections, and their relationship to ''vulnerable plaques'' and thrombosis [62][63][64][65]. If inflammation plays an important role in conversion from atherosclerosis to clinical disease, then epidemiology studies need better measures of ''inflammation,'' e.g.…”
Section: Discussionmentioning
confidence: 99%
“…40 Large studies have also shown that influenza vaccination has a marked protective effect against primary and secondary cardiovascular events. [41][42][43] Despite these clear protective properties of influenza vaccination, the data supporting a direct effect of influenza virus on atherosclerosis is weak. To date, the presence of influenza viral DNA or protein within human atherosclerotic plaques have not been reported.…”
Section: Virusesmentioning
confidence: 99%